Spectroscopic Imaging of the Sun with MeerKAT: Opening a New Frontier in Solar Physics - Devojyoti Kansabanik; Surajit Mondal; Divya Oberoi; James O. Chibueze; N. E. Engelbrecht; R. D. Strauss; E. P. Kontar; G. J. J. Botha; P. J. Steyn; Amoré E. Nel (The Astrophysical Journal, 2024)
Solar radio emissions provide several unique diagnostics to estimate different physical parameters of the solar corona, which are otherwise simply inaccessible. However, imaging the highly dynamic solar coronal emissions spanning a large range of angular scales at radio wavelengths is extremely challenging. At gigahertz frequencies, MeerKAT radio telescope is possibly globally the best-suited instrument at present for providing high-fidelity spectroscopic snapshot solar images. Here, we present the first published spectroscopic images of the Sun made using the observations with MeerKAT in the 880–1670 MHz band. This work demonstrates the high fidelity of spectroscopic snapshot MeerKAT solar images through a comparison with simulated radio images at MeerKAT frequencies. The observed images show extremely good morphological similarities with the simulated images. Our analysis shows that below ∼900 MHz MeerKAT images can recover essentially the entire flux density from the large angular-scale solar disk. Not surprisingly, at higher frequencies, the missing flux density can be as large as ∼50%. However, it can potentially be estimated and corrected for. We believe once solar observation with MeerKAT is commissioned, it will enable a host of novel studies, open the door to a large unexplored phase space with significant discovery potential, and also pave the way for solar science with the upcoming Square Kilometre Array-Mid telescope, of which MeerKAT is a precursor.